IMPLEMENTASI TQM TERHADAP MUTU INSTITUSI DALAM LEMBAGA PENDIDIKAN - Suhermanto, Suhermanto; Anshari, Anshari (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2018)
Earing the word education is certainly no stranger to the public. Education is addressed with school and learning. The word education in terms of language is derived from the word